2008
DOI: 10.1002/jbm.a.32183
|View full text |Cite
|
Sign up to set email alerts
|

Titanium IV ions induced human osteoclast differentiation and enhanced bone resorption in vitro

Abstract: There is increasing evidence that titanium (Ti) ions are released from orthopedic implants, with concentrations in the range of 1 microM in tissue and blood, and may play a role in aseptic loosening of orthopedic implants. This study investigated whether Ti(IV) ions induce differentiation of monocytic osteoclast precursors into osteo-resorptive multinucleated cells and influence the activation and function of in vitro generated osteoclasts. Human monocytes and in vitro generated osteoclasts were exposed to 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
70
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 40 publications
0
70
0
Order By: Relevance
“…32,33 These may induce hypersensitivity reactions by activation of the immune system, 32,34 and may potentially cause numerous local and systemic negative effects, such as inflammation, infection, pain, effusion, urticaria, or wound healing disorder. 35,36 During the Relative metabolic activity (%) Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 These may induce hypersensitivity reactions by activation of the immune system, 32,34 and may potentially cause numerous local and systemic negative effects, such as inflammation, infection, pain, effusion, urticaria, or wound healing disorder. 35,36 During the Relative metabolic activity (%) Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the exact pathophysiologic mechanisms leading to aseptic implant failure (commonly known as aseptic loosening) remain unclear. Aseptic loosening is thought to be caused by increased osteolytic activity at the bone-implant interface, ultimately leading to a loss of fixation (3)(4)(5). Infiltration of adaptive immune cells including B-and T-lymphocytes, dendritic cells and monocytes has been observed in histologic sections of peri-implant tissues retrieved from patients with aseptic loosening (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] We have previously demonstrated that metal ions (such as titanium) directly induce the differentiation of osteoclast precursors towards mature OC, able of effective bone resorption. 16 Furthermore, once released into the systemic blood circulation, the metal ions bind to serum proteins and form haptens or hapten-like complexes, which are considered to be relevant antigens recognized by T lymphocytes and candidates for eliciting hypersensitivity reactions. 5,17 Exposed to metal-protein complexes, T lymphocytes proliferate and differentiate to produce effectors such as interleukin (IL)-6, IL-1a/b, interferon-gamma (IFN-g) and tumor necrosis factoralpha (TNF-a) that trigger a particular immune response.…”
mentioning
confidence: 99%